Carving Spaces of an Otherwise Within Urban Uncertainties On Sudanese People on the Move Creating Own Possibilities in Cairo - Mohamed, Iman (AUC Knowledge Fountain, 2022)
With the increased urbanization of the world since the 1940s, people continue to be increasingly moving to cities. People are attracted to the city to access services and opportunities. However, the increased presence of persons on the move in the city comes with heightened bordering, augmented policing, and the involvement of more actors in the governance of people on the move. Against this, there are debates around understanding the urban space, its risks, and opportunities for all people dealing with it, including those on the move. This thesis thus looks at the urban space in Cairo that is uncertain, wherein its unfoldings are often not projected. It traces how Sudanese people on the move in Ard ElLewa manage to deal with Cairo’s uncertainty and hardships in their everyday lives. It explores whether urban uncertainty is an opportunity or an obstacle for people dealing with it. How the limitations, created by the urban uncertainty, manifest against the opportunities and spaces that could be created through it. Through Sudanese people on the move’s navigations of Cairo’s uncertainty, the thesis brings into dialogue the question of representation and voice, questioning whether people on the move’s portrayal as ‘passive’ and ‘helpless’ renders visible.